POLITISASI TAFSIR AYAT AL-QUR’AN - Ade Naelul Huda; Muhamad Azizan Fitriana; Syaifullah Syaifullah (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
This article aims to explain the history of the politicization of the interpretation of Qur'anic verses and how it has implications for misappropriating the meaning of the Qur'an. The politicization of the interpretation of qur'anic verses is carried out because there is no way to change the text of the Qur'anic verses. So that the legitimacy of the Qur'an for political celebrations finds its way through interpretation. The politicization of the interpretation of qur'anic verses has always been a trend due to the attachment of the holy book of the Qur'an and the interpretation of the Qur'an with Muslims. So that  the political views and choices that arelegitimized by the  Qur'anic verses and the interpretation of the Qur'anic verses can be easily accepted.  Thismethod uses a descriptive qualitative method through a historial approach.  Various data are obtained through  literature studies. The results of the study found that the politicization of the interpretation of qur'anic verses has been used by the Khawârij group since the time of the companions of 'Alî ibn Abi Talib in the events of tahkîm and continued from time to time, including in Indonesia. Theolitization of the interpretation of qur'anic verses in addition to sering causing divisions among Muslims, also often leads to changes in  the meaning of the Qur'an. The politicization of the interpretation of qur'anic verses arises due to political interests, hatred factors, and ignorance of verse users in the interpretation method so as to violate existing interpretations. This research contributed to uncovering the history of the use of interpretations  of the holy verses of the Qur'an for political and power purposes.